The Benefit of the Optimized Formula of Yinxieling in Psoriasis Vulgaris via Regulation on Autophagy Based on microRNA Expression Profile and Network Pharmacology Analysis - Lu Y; Pan S; Li W; Qi Y; Li L; Yan YH; Wei J; Yao DN; Wu J; Deng H; Ye S; Chen H; et al. (Dove Medical Press, 2024)
Yue Lu,1- 3,* Simin Pan,4,* Wenzhen Li,5 Yao Qi,6,7 Li Li,1- 3 Yu-Hong Yan,1- 3 Jianan Wei,1- 3 Dan-Ni Yao,1- 3 Jingjing Wu,1- 3 Hao Deng,1- 3 Shuyan Ye,1- 3 Haiming Chen,1- 3 Qubo Chen,1- 3 Hengjun Gao,6,7 Ling Han,1- 3 Chuanjian Lu1- 3 1State Key Laboratory of Dampness Syndrome of Chinese Medicine, The Second Affiliated Hospital of Guangzhou University of Chinese Medicine (Guangdong Provincial Hospital of Chinese Medicine), Guangzhou, People's Republic of China; 2Guangdong Provincial Key Laboratory of Clinical Research on Traditional Chinese Medicine Syndrome, Guangzhou, People's Republic of China; 3Guangdong-Hong Kong-Macau Joint Laboratory on Chinese Medicine and Immune Disease Research, Guangzhou University of Chinese Medicine, Guangzhou, People's Republic of China; 4The Second Clinical College, Guangzhou University of Chinese Medicine, Guangzhou, People's Republic of China; 5The Clinical College of Acupuncture Rehabilitation, Guangzhou University of Chinese Medicine, Guangzhou, People's Republic of China; 6Shanghai Molecular Medicine Engineering Technology Research Center, Shanghai, People's Republic of China; 7Shanghai National Engineering Research Center of Biochip, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Ling Han; Chuanjian Lu, Email linghan99@gzucm.edu.cn; lcj@gzucm.edu.cnBackground: Psoriasis is a widespread chronic, immune-mediated skin disease with frequent recurrences, and is extremely harmful to the physical and mental health of patients, causing enormous suffering and exerting considerable economic burdens on the health care system as a whole. In more than a decade of clinical use, the optimized formula of Yinxieling (PSORI-CM01) has consistently demonstrated its effectiveness for treating psoriasis. However, its underlying mechanism remains largely unexplored.Methods: The network pharmacology analysis was conducted to predict the mechanism and protective effect of PSORI-CM01 in treating psoriasis. Subsequently, we collected blood samples from 21 patients with psoriasis as part of a randomized, double-blind, and double-dummy clinical trial for microRNA expression profiling. Finally, it was experimentally confirmed that PSORI-CM01 improved psoriasis by regulating miR-20a-3p and miR-3184-3p expression.Results: As a result of the network pharmacology analysis, PSORI-CM01 improved psoriasis through the regulation of autophagy, cellular apoptosis, cellular proliferation, and anti-inflammatory processes. In the target-miRNA regulatory network, these key targets were mainly associated with the regulation of hsa-miR-20a-3p, hsa-miR-155-5p, has-miR-3184-3p, hsa-miR-328-3p and hsa-miR-124-3p. Based on the microRNA expression profiling results, the PSORI-CM01 treatment group exhibited five up-regulated genes and 16 down-regulated genes compared with the healthy control group. In particular, miR-20a-3p and miR-3184-3p were the primary differentially expressed microRNAs, and they were significantly enriched in the signaling pathways involving autophagy, apoptosis, proliferation, and anti-inflammation. Further experiments confirmed that PSORI-CM01 effectively regulates miR-20a-3p and miR-3184-3p, resulting in increased autophagy.Conclusion: We demonstrated by combining network pharmacology and clinical studies of miRNA expression profiles in PBMCs that PSORI-CM01 effectively modulated miR-20a-3p and miR-3184-3p, leading to an increase in autophagy and a decrease in keratinocyte proliferation.Keywords: PSORI-CM01, Psoriasis vulgaris, MicroRNA expression profile, network pharmacology, autophagy